Whoso List to Find?: Hard Facts, Soft Data, and Women Who Count. Issue 1 (1st March 2022) - Mazzola, Elizabeth
Abstract: Seeing what Englishwomen saw in the early modern period brings them into view in a variety of new ways, many of them managed and enhanced by the machinery of cheap print. In contrast with Petrarchan poetry, which imagined women with fear and described love as plague, print established other models of health and wellness, and other ways of registering women's powers. Women known as searchers who were charged to enter houses and locate plague rather than flee from it shared their findings with town officials who printed up statistics in weekly Bills of Mortality . The searcher was both a 'harbinger of disaster' and a tool of recovery, and popular ballads of the time frequently deploy her example along with her abilities to avoid ruin and register signs of life. These ballads supply alternatives to Petrarchan demographics, and I examine the ways early modern female poets draw upon their methodology, too.